A study of motivations, deterrents, needs, skills and attitudes towards research undertakings of public secondary teachers - Pornel, Jonny B.; Firmase, Josephine T. (Danyag :the UPV journal of humanities and social sciences, 2010)
"This paper determined what could motivate and deter public high school teachers form conducting research and what training programs and support would be needed by them to improve their research productivity. It also explored the factors underlying the teachers' attitude towards research undertakings. The respondents of this study were 95 teachers out of the 170 regular teachers employed at a public high school in Iloilo City. The results showed that professional growth was their prevalent motivation in doing research. The primary deterrent to doing research was time availability. To improve research productivity, the teachers cited the need for financial support and research training programs. The respondents were found to have low level of skills in statistical processes and qualitative data gathering. Their attitude towards research undertakings was found to be positive and the factors underlying this attitude were: disposition towards research processes, appreciation of research products and research diligence. The following were found in this study to be significant correlates of research productivity: appreciation or research product, skills in data gathering, and skills in doing case study."